ANALISIS MEDIA SOSIAL INSTAGRAM DALAM MEMBENTUK KESADARAN POLITIK MAHASISWA GEN Z DI KOTA DENPASAR - I Gusti Ayu Bintang Dwijayanthi; I Nyoman Subanda; Nuning Indah Pratiwi; Kadek Devi Kalfika Anggria Wardani (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze how political content on Instagram shapes the political awareness of Generation Z students during the 2024 Bali Regional Election (Pilkada), using the Agenda Setting theory as the main analytical framework. Employing a descriptive qualitative approach, this research examines three levels aof agenda setting: media agenda, public agenda, and policy agenda, alongside the cognitive, affective, and evaluative dimensions of political awareness. The findings reveal that Instagram plays a significant role in directing the political issues considered important by Gen Z, particularly through the viral circulation and high frequency of political content during the election period. These digital discussions not only influence public dialogue among students buat also stimulate responses from candidates, contributing to the formation of policy agendas. Furthermore, Instagram enhances students (cognitive) awareness by increasing their political knowledge, triggers emotional responses toward candidates and political issues (affective), and strengthens their critical evaluation of information (evaluative), ultimately encouraging more informed and conscious voting behavior. Overall, this stufy highlights Instagram as an effective digital political arena that fosters political awareness and engagement among Generation Z during the 2024 Bali Regional Election.